The Urgency of The Mediator's Code Of Ethics As An Independent Third Party In Resolving The Parties' Dispute - Badru Jaman, Ujang; Armansyah, Armansyah (IJBLE Scientific Publications Community Inc., 2024)
This research was conducted with the aim of knowing how the position of the mediator as an independent party in case dispute resolution and how the urgency of the mediator's code of ethics in violating the code of ethics. This research uses normative juridical research methods. the position of the mediator has an important role as a neutral party in charge of facilitating dialog between the parties to the dispute. and the Mediator's Code of Ethics has great urgency in the context of dispute resolution as an independent third party. By ensuring that mediators operate with integrity and neutrality, the Code forms the basis for ethical behaviour that supports a fair mediation process. The existence of this independent third party is critical in creating an environment that allows disputants to communicate openly and honestly. The Code of Ethics ensures that the mediator carries out his or her role with fairness, keeps information confidential and avoids conflicts of interest. With the Code of Ethics, the mediator not only acts as a facilitator but also as a holder of high standards in ensuring fairness and openness in dispute resolution. The Mediator Code of Conduct therefore plays a crucial role in upholding ethical norms that ensure trust and success of the mediation process.